BRIDGING THE GAP FROM CLINICAL PRACTICE TO ACADEMIC OUTPUT: A MIXED-METHODS SYSTEMIC ANALYSIS OF HEALTH RESEARCH CAPACITY IN A TRANSITIONAL LOWER-MIDDLE-INCOME COUNTRY SETTING (Vietnam Journal of Community Medicine, 2026)
Objective: To provide an expanded institutional analysis of hospital-based research capacity and propose governance-oriented strategies for strengthening scientific research systems in a transitional lower-middle-income country (LMIC) setting, utilizing a public general hospital in Vietnam as a case study (2019–2024).Methods: A convergent parallel mixed-methods design was employed for this secondary institutional analysis, adhering to the Good Reporting of a Mixed Methods Study (GRAMMS) guidelines. Quantitative information included institutional scientific research records from 2019 to 2024 and a survey among 316 healthcare workers. Qualitative findings were derived from eight in-depth interviews and four focus group discussions. Analysis focused on institutional research capacity using the World Health Organization’s six health system building blocks framework, augmented by the systemic capacity strengthening framework for health policy and systems research (Mirzoev et al., 2022) to capture complex organizational dynamics. Data integration occurred at the interpretation level utilizing a joint display methodology.Results: Scientific research activities at Trung Vuong Hospital demonstrated sustained institutional engagement but modest productivity and limited sustainability. During 2019–2024, the hospital implemented 55 scientific research projects and 147 quality improvement initiatives. Institutional-level projects predominated, while higher-level research projects and international publications remained limited (publication-to-project ratio of 25.5%). Research participation was concentrated among physicians, senior staff, and healthcare workers with postgraduate education. Major institutional barriers included heavy clinical workload, fragmented governance, limited methodological and statistical support, insufficient funding mechanisms, fragmented digital systems, and limited translation of research findings into clinical practice. The absence of a dedicated institutional research support structure emerged as a major organizational weakness, exacerbated by a lack of protected research time and structural inequities in academic power distribution among diverse clinical disciplines. Qualitative narratives highlighted the contradictory environment where frontline staff recognize the value of research but are deterred by complex administrative labyrinths and the necessity to self-fund small-scale projects.Conclusion: Strengthening hospital-based research capacity requires coordinated institutional reform rather than isolated encouragement of individual participation. Public hospitals should establish dedicated research governance structures, develop centralized digital research databases, strengthen methodological and publication support, integrate research into quality improvement systems, and create sustainable academic incentive mechanisms. Transitioning from a focus on individual capacity building to systemic ecosystem governance is imperative to elevate LMIC hospitals from mere data extraction sites to equitable centers of health knowledge production.
Keywords: research capacity; hospital governance; hospital-based research; health systems; Vietnam; scientific research management; mixed-methods; learning organization; systemic capacity.